Evaluación del arreglo agroforestal Morella pubescens H&B Ex Willd Wilbur asociado con Tigridia pavonia y Zea mays en el municipio de Sibundoy departamento del Putumayo - Hidalgo M., Ingrid Lorena; Pantoja M., William Orlando; Vélez L., Jorge Alberto (Revista de Ciencias Agrícolas, 2009)
The work was carried out between June of the 2006 and April of the 2007 in the Municipality of Sibundoy, located to 2200 m.a.i.s., temperature average of 16° C, annual precipitation of 750 at 1586 mm and 669.9 hours sun/year (EOT Sibundoy, 2002). In the study they settled down and they evaluated four treatments: laurel inserted with Watsimba (T1); laurel inserted with corn (T2), laurel with Watsimba and corn (T3) and laurel as monocultivo (T4); some agronomic variables were also determined for the cultivations in the system. The statistical design was at random of complete blocks with four treatments and three repetitions, developing Andeva for the trees and test of t for cultivations. When evaluating the arboreal component in the variable height, diameter and number of branches (primary and secondary), they didn’t present significant statistical differences among the treatments; with regard to the covering it was statistical differences in the month of June being the treatment two the one that reached the biggest covering, obtaining a value of 28.65 cm2. The test of t for watsimba didn’t indicate significancia among the treatments, for the variables: height, number of bulbs for plant, diameter and weight of the bulb. For the corn in the variable height the results height show statistical differences among treatments to the 120 days, being the treatment two the one that presents bigger average (78.41cm). with regard to the number of ears for plant were not statistical differences. Simultaneously the production of the cultivations was evaluated keeping in mind the yield of each one of them for each treatment; finding that the T1 presents significant statistical differences in front of the T3. As for the yield of the corn they were not significant statistical differences among treatments. The partial analysis of costs, shows that the smallest production cost and maintenance for hectare of the evaluated treatments the it presented the treatment four (Witness) that was of 6’677.083. The biggest production cost and maintenance presented it the treatment three (L//W//M) that was of 10’097.222.